Microhardness and water solubility of expired and non-expired shelf-life composites. Issue 1 (January 2019) - Eliguzeloglu Dalkilic, Evrim; Donmez, Nazmiye; Kazak, Magrur; Duc, Bugra; Aslantas, Akif
Background: The aim of this study was to determine the Vickers hardness and water solubility of expired and non-expired shelf-life bulk-fill and conventional dental composite material. Methods: Four different expired (E) (after 6 months) and non-expired (N) shelf-life composite resin materials (Clearfil Majesty ES-2 Enamel, Clearfil Majesty ES-2 Dentin, Tetric N-Ceram Bulk-Fill, and Tetric N-Ceram) were used. For each tested material, seven specimens were prepared and polymerized with a light curing unit. Vickers hardness measurements were made on the top and bottom surfaces. For the water sorption test, initially all specimens were weighted, the thickness and diameter of each specimen were measured, and the average volume of specimen was calculated. Then, each specimen was immersed in distilled water and kept in an incubator for 7 days and finally weighed again. Results: There was not any statistically significant difference between the microhardness results of expired and non-expired shelf-life composites on the top and bottom surfaces (p > 0.05). No significant difference was determined between the non-expired shelf-life composite materials on the top surfaces (p > 0.05). Non-expired Clearfil Majesty ES-2 Dentin showed lower microhardness than non-expired Tetric N-Ceram Bulk-Fill and non-expired Tetric N-Ceram on the bottom surface (p < 0.05). Expired Clearfil Majesty ES-2 Dentin showed lower microhardness results than expired Tetric N-Ceram Bulk-Fill on the top and bottom surfaces (p < 0.05). There was not any significant difference between the water sorption results of expired and non-expired shelf-life composites (p > 0.05). Expired Clearfil Majesty ES-2 Dentin showed higher water sorption than expired Tetric N-Ceram E-TN (p < 0.05). Conclusion: Expiration date did not affect the microhardness and water sorption of bulk-fill and conventional composites. The hardness and water sorption of the composite materials varied depending on the type of composites.